Pendampingan Pembuatan NIB Melalui OSS Dan Desain Kemasan Produk Untuk Pengembangan UMKM Desa Puncak Menuju Smart Village - Andriyanto, Gian Anggraeni; Wibowo, Sandi Nasrudin (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The number of MSMEs in Puncak Village, Cigugur District is increasing because people are motivated to start their own businesses. There are still many MSME players in the Puncak Cigugur Village area who do not know or understand the legality of their business, in this case the importance of having an NIB. This is because some people understand that obtaining a business license is complicated and time-consuming. NIB currently plays a very important role in the business of economic actors. The provision of a Business Identification Number (NIB) is carried out through OSS (Online Single Submission). In addition, many MSMEs in Puncak Village do not yet have a logo or label on their product packaging. Some MSMEs that already have a logo were redesigned. The method used in this community service is education on the procedures for making a Business Identification Number (NIB) and this activity is carried out by door to door MSMEs in Puncak Village. The output of this service is the issuance of a Business Identification Number (NIB) and new product packaging and label designs for MSME players in Puncak Village, Cigugur District. To support Puncak village as a smart village, by supporting MSMEs to have NIB and packaging for MSME players. One of the main indicators of achieving a smart village is a smart economy, because MSMEs are the main actors of economic activities in the village. Therefore, it is necessary to strengthen MSME stakeholders in Puncak Village, Cigugur District, Kuningan Regency.